A Data-Informed Approach for Identifying Move-on Encounter Thresholds for Vulnerable Marine Ecosystem Indicator Taxa - Geange, Shane W.; Rowden, Ashley A.; Nicol, Simon; Bock, Tiffany; Cryer, Martin (Frontiers in Marine Science, 2020)
The United Nations General Assembly has called for the adoption of conservation management measures to protect vulnerable marine ecosystems (VMEs) from significant adverse impacts outside of areas of national jurisdiction. In response, many regional fisheries management organisations (RFMOs) have implemented move-on rules triggered by encounter threshold levels for the biomass of VME indicator taxa retained as bycatch. However, due to uncertainty of the relationships between catch, catch efficiency and the in-situ biomass of VME indicator taxa, move-on rules alone may not be enough to prevent significant adverse impacts on VMEs. Although spatial management measures present one possible solution to these concerns, a lack of empirical data on the distribution of VMEs within the high seas means spatial management is often informed by model predictions of the spatial distribution of VME indicator taxa. Given the uncertainty associated with predicted distributions, move-on rules can provide immediate responses when spatial management measures may not be providing the expected conservation benefits. Using bycatch data from 9,771 New Zealand bottom trawls within the South Pacific RFMO Convention Area, we illustrate a data-informed approach for selecting high move-on encounter thresholds that may suggest the predicted distributions of VME taxa used to underpin spatial management are highly inaccurate. The reasoning that high thresholds act as a safeguard against uncertainty in the performance of spatial management measures requires untested assumptions regarding the level of permissible bycatch before further management action is required, with the acceptance of those assumptions a management decision balancing the sensitivity of the move-on rule with uncertainty regarding the effectives of the spatial management measures. Additional work is required to support these management decisions, including the determination of taxa-specific catchability estimates, and the seafloor density/biomass of VME indicator taxa that represents a VME. Obtaining this information will allow for the identification of encounter thresholds that are more ecologically meaningful. In the interim, the choice of thresholds should be re-evaluated as more experience with their application is gathered.